Enabling pupils to flourish: six evidence-based principles of whole-school wellbeing promotion - Rowan Edwards; Jennifer Byrne; Marcus Grace (Frontiers Media S.A., 2024)
Schools have become increasingly important as health promotion settings, seeking to improve pupils' health and wellbeing through adopting a whole-school approach. A strong evidence-base highlights that focusing on the social, emotional and psychological aspects of pupils' wellbeing enables them to flourish, enjoy life and be better equipped to overcome challenges. However, it is acknowledged that further evidence is required regarding: (1) what happens in primary schools, (2) the impact of the English education system, (3) complexity and context, and (4) capturing children's voices. This article, therefore, addresses these gaps by asking the question: How do schools use whole-school wellbeing promotion to enable pupils to flourish? Taking an exploratory approach the study used a three-phase, mixed methods design to address the research problem by undertaking a systematic literature review, a secondary data analysis and a case study to capture multiple stakeholder voices including pupils. As appropriate for this research design, the findings from each phase were integrated into an overarching analysis which is presented in this article. Six broad principles formed consistent threads across the findings: (1) enabling children to flourish, (2) integrating wellbeing with key school goals, (3) promoting wellbeing and building capital, (4) building on virtuous cycles, (5) managing complexity and context, and (6) evaluating wellbeing promotion through listening to different voices. As well as presenting new knowledge addressing the identified research gaps, this study has demonstrated that schools can avoid 'reinventing the wheel' by adopting existing practices and resources and adapting them to their own setting. It is, therefore, hoped the six evidence-based principles of this study are equally transferable to schools within the English education system and more broadly. In addition, the paper highlights recognized challenges to staffing and resourcing and raises the question over whether schools receive sufficient funding to deliver the whole-school initiatives that government recommends. This article provides readers with an exploration of what has been achieved in schools and it is outside its scope to address specific issues about funding and other practical logistics for implementing whole-school wellbeing promotion, therefore further research is recommended.